Analisis Biomekanika Gerakan Atlet Renang untuk Optimalisasi Latihan - Wijono Sukaputra Agussalim; Trifena Ruth Clara (CV. Aksara Global Akademia, 2025)
This study aims to analyze the effect of body angle variations on propulsion force, drag coefficient, and freestyle swimming performance using a biomechanical approach. Movement efficiency in swimming plays a crucial role in improving athlete performance. This study employed a quantitative experimental design with university or club-level swimmers with at least three years of training experience as subjects. Subjects were selected through purposive sampling with the criteria of being healthy, familiar with freestyle techniques, and willing to follow the research procedures. The instruments used included 3D motion capture to record body angles and movement coordination, force sensors to measure propulsion force and drag coefficient, and a timekeeping system to calculate average speed. The body angle variations tested were 0°, 15°, and 30°, each with three replications. Data were analyzed using descriptive statistics to describe the mean, standard deviation, and data distribution, and comparative statistics (ANOVA or paired t-test) to compare performance between angle variations. The results showed that a 15° body angle provided optimal performance, with increased average speed and propulsion efficiency compared to 0° and 30° body angles. These findings confirm that body angle regulation plays a crucial role in reducing water resistance and increasing propulsion. The study concluded that a 15° body angle is the ideal position for improving freestyle swimming performance. Further research is recommended to expand the number of subjects, explore variations in other swimming strokes, and integrate physiological data for more comprehensive results.